RESPECTFUL WORKPLACE POLICY TO CONCEIVE A SECURITY CONSCIOUSNESS AND GENDER EQUALITY AS AN IMPLEMENTATION OF AKHLAK CORE VALUES IN STATE-OWNED ENTERPRISES ENVIRONMENT - Susilowati, Endang; Sadirsan, Erwin Susanto (UI Scholars Hub, 2023)
A safe work environment, mutual respect, freedom from discrimination, harassment, violence, gender inequality, discrimination of women is highly coveted in the Indonesian work environment. In State-Owned Enterprises there are still issues of harassment, gender inequality, violence, and women's opportunities to become leaders in the workplace. In 2021, the number of women leaders in workplace is still below 10%. The Ministry of State-Owned Enterprises is aiming to increase the representation of women in the Board of Commissions or Executives, and one level below the Board of Executives by 25% in 2023. The purpose of this research is to analyse women's issues in the State-Owned Enterprises environment related gender inequality, harassment, and violence; identify variables which affects to work engagement and harassment. The research used quantitative methodology with a questionnaire survey and descriptive analysis completed in order to determine the differences between demographic groups, gender, age groups, positions in the company and marital status. The research is conducted in Indonesian State-Owned Enterprises, this specific location of research is the novelty of this research. The result of this research is the implementation of the policies of mutual respect in workplace that conceive productive work environment, respect women, and protect human dignity, free from harassment, create gender equality and uphold human rights.